Factors associated with pregnancy-related anxiety: a health facility-based study - Wahyuni, Sri; Pramono, Noor; Hadisaputro, Suharyo; Ediati, Annastasia (International Journal of Public Health Science (IJPHS), 2024)
Pregnancy is a critical phase for human beings, which can lead to various mental health issues, including anxiety. It is important to recognize that pregnancy-related anxiety can increase over time and should be addressed. This study aimed to explore the multifactor of pregnancy-related anxiety during the first trimester. A cross-sectional health facility-based study was conducted in four Semarang, Central Java, Indonesia public health centers. A total of 129 pregnant women were involved and identified some exposures, such as socio-demographics, nausea and vomiting during pregnancy (NVP), emotion regulation, social support, and anxiety levels. The average age of participants was 27.3 years. Their anxiety level was moderate to severe (37.2%), and 62.8% were identified as having mild anxiety. This study suggests that pregnant women who lack social support (AOR=4.105; 1.824-9.237) and emotion dysregulation (AOR=2.749; 1.244-6.075) were identified as the risk factors of maternal anxiety during the first trimester. Being employed (AOR=0.410; 0.182-0.922) protects the high anxiety during pregnancy. This study suggests that the lack of social support, including social interaction most influences pregnant women’s mental well-being. Therefore, it may be helpful to establish an intervention plan that strengthens social support to improve maternal mental well-being.